Before we are born essentials of embryology and birth defects - Moore, Keith L. (Saunders/Elsevier, 2013)
Before We Are Born: Essentials of Embryology and Birth Defects, by Drs. Keith L. Moore, T.V.N. Persaud, and Mark G. Torchia, allows you to efficiently and quickly assimilate the most important concepts related to this subject. Concise and richly illustrated, this popular book delivers the embryology knowledge you need in a highly efficient, reader-friendly manner. You can also access the complete contents online at www.studentconsult.com, along with 17 remarkable animations, downloadable illustrations, additional review questions and answers, and more. Access the full contents of the book online at www.studentconsult.com - as well as 17 remarkable animations that bring normal and abnormal embryological development to life, downloadable images, and hundreds of additional review questions and answers to test your mastery of the material. Focus on the most need-to-know information with coverage masterfully distilled from The Developing Human, 8th Edition - the more comprehensive and in-depth embryology textbook by Drs. Moore, Persaud, and Torchia. Study efficiently and flexibly thanks to the book's user-friendly full-color format and portable size. Effectively prepare for exams with review questions and answers at the end of each chapter.